Halophilic archaea cultivated from surface sterilized middle-late eocene rock salt are polyploid - Jaakkola, Salla T.; Zerulla, Karolin; Guo, Qinggong; Liu, Ying; Ma, Hongling; Yang, Chunhe; Bamford, Dennis H.; Chen, Xiangdong; Soppa, Joerg; Oksanen, Hanna M. (PLoS ONE, 2016)
Peer reviewed